STUDY THE VARIATIONS OF WEATHERING LEVELS FOR SOME SOILS FORMED UNDER DIFFERENT CLIMATEIC CONDITIONS / NORTHERN IRAQ - Saleh Mawlood; Qahtan D. Essa (Mesopotamia Journal of Agriculture)
Nine soil samples were selected from three different locations in Ninavah and Duhok Governorates. The locations included Makhmour, Hamdania and Zakho. The studied areas were selected according the variation of annual temperature and rainfall. Soil orders of Makhmour and Hamdania are both within Aridisols, but Zakho soil is a Vertisols. Soil profiles were described according to USDA and three soil samples from each profile were collected from three depths (0-20, 20-40 and 40-60 cm). Chemical analysis was conducted using (XRF) Technique. Calculation of weathering parameters has been done such as chemical index of variations (CIA), index of chemical variation (ICV) and weathering index (WI). Results of weathering parameters included that the highest levels of weathering levels was found in Zakho soil (Average annual rainfall 550 mm) and the lowest weathering levels in Makhmour soil (Average annual rainfall 240 mm). Results of XRF Analysis also showed a clear increasing in immobile oxides of (SiO2, Fe2O3 and Al2O3) and trace (rare) elements (ZrO, MnO and TiO2) in Zakho soil and decreased in Makhmour soil. However the mobile oxides of (CaO) and the loss in ignition was increased in Makhmour soil and gradually decreased in Hamdania and reach its lowest levels in Zakho soil.